Analysis of the treatment cost of HIV/AIDS in Turkey - Kockaya, Guvenc; Zengin, Tuba Elbir; Yenilmez, Fatma Betul; Dalgic, Canan; Simten Malhan, Simten Malhan; Cerci, Pamir; Oksuz, Ergun; Unal, Serhat (Farmeconomia. Health Economics and Therapeutic Pathways, 2016)
OBJECTIVE: Infection with the human immunodeficiency virus (HIV), the causative agent of acquired immune deficiency syndrome (AIDS), is a major global health problem. Patients with HIV can live normal lives with today’s new treatment options. As the treatment is generally successful, the life expectancy of patients infected with HIV is rising. As a result, the economic burden of HIV treatment on health systems is set to increase. According to the Ministry of Health, there were more than 6000 HIV-positive patients in Turkey in 2013. The aim of this study was to determine the direct costs of HIV treatment in Turkey.METHOD: A retrospective data analysis was performed from the reimbursement agency perspective. Data for 252 patients at a university hospital in Ankara from 2001 to 2012 were used for the analysis. The average costs of treatment per HIV patient and the average costs per HIV patient, depending on the state of the patient’s health, were calculated. The latter was determined according to the number of CD4 cells/ml, as defined by the CDC’s classification system for HIV infection. The cost of treatment was calculated based on published reimbursement prices in 2013, per patient per year.RESULTS: The CD4 values of 25.3%, 29%, and 45.7% of the 252 patients were 300 cells/mm3, respectively. The treatment costs per patient per year for 2013 for those with CD4 values of 300+ cells/mm3 were $ 5,637.04, $ 2,211.54, and $ 2,182.35, respectively. The weighted average of the treatment cost per patient was $ 3,344.64 for 2013.CONCLUSION: This analysis is unique to Turkey and calculates the cost only of HIV treatment in Turkey. Lower CD4 values are associated with higher treatment costs. Appropriate HIV treatment is crucial for controlling CD4 values and lowering the treatment costs of HIV patients. These findings need to be considered by policy makers who may need to focus on HIV.